Role of ICT in Saudi women empowerment and their participation in labor market - Khan, Mohd Naved; Aziz, Ghazala; Asif, Mohammad (Edelweiss Applied Science and Technology, 2025)
The objective of this empirical study is to evaluate the extent of economic empowerment in Saudi Arabia and examine the impact of information and communication technologies (ICTs) on women's empowerment and their participation in the labor market. This study also aims to evaluate the level of economic empowerment among Saudi women and explore how it can drive economic development and contribute to the 2030 vision. Additionally, it will identify the barriers and challenges Saudi women face in economic empowerment and propose realistic solutions. The research design for the study is based on primary data. The opinions for the study are collected through a survey form, and the respondents are women from Saudi Arabia. The study will sample approximately 400 women respondents from various organizations. The results of the study clearly show that, in the present context, women in Saudi Arabia are much more empowered compared to previous decades. The roles of ICT support women in creating their own respective worlds where they are proving themselves as skilled labor. In the present scenario, with the help of ICT tools and technology, women in Saudi Arabia lead in the labor market and play a crucial role in the economy and welfare as well.